Peptide-based drug as atherosclerosis multitarget therapy from Lytechinus variegatus spine: An in silico study - Arisanty, Dessy; Khairani, Salsabila P.; Nathaniel, Kevin; Wahyudi, Dhyani P.; Kamila, Isna C.; Maharani, Malya CS.; Theodora, Eillen; Budianto, Raymond E.; Shofiy, Alifya R.; Nugraha, Ikwandi C.; Aaliyya, Zaki S.; Rahman, Awalil RK.; Ariouso, Al H. (Narra Sains Indonesia, 2025)
Atherosclerosis is a leading cardiovascular disease characterized by the buildup of plaques within arterial walls. The aim of this study was to investigate the potential of peptides derived from Lytechinus variegatus spines as novel therapeutic agents for atherosclerosis using an in silico approach. Key proteins involved in atherosclerosis were selected as target proteins: vascular endothelial growth factor receptor (VEGFR), protein kinase B (AKT1), epidermal growth factor receptor (EGFR), mitogen-activated protein kinase 8 (MAPK8), and endothelin-1 (ET-1). Comprehensive analysis involving ligand and protein preparation, toxicity, and allergenicity assessments, absorption, distribution, metabolism and excretion (ADME) predictions, and molecular docking were conducted to evaluate the safety, pharmacokinetic properties, binding affinity (kcal/mol), root mean square deviation (RMSD) (Å), as well as a 2D and 3D visualization. Toxicity predictions revealed that peptide 9 was non-toxic and non-allergenic, with a lethal dose 50 (LD50) of 3,000 mg/kg, indicating its safety. Peptide 9 demonstrated the most promising results, effectively inhibiting VEGFR2 (-10,90 kcal/mol), AKT1 (-10,56 kcal/mol), EGFR (-9,82 kcal/mol), MAPK8 (-9,64 kcal/mol), and ET-1 (-11,41 kcal/mol) with strong binding affinities and specificity. These interactions suggested that peptide 9 from Lytechinus variegatus spines may serve as a competitive multitarget inhibitor, offering potential multitarget therapeutic activity against atherosclerosis. Peptide 9 also had high water solubility and did not affect the concentration or excretion of other drugs or compounds, minimizing the risk of drug-drug interactions.